Antioxidant and Antiproliferative Activity of Allium ursinum and Their Associated Microbiota During Simulated in vitro Digestion in the Presence of Food Matrix - Stanisavljević, Nemanja; Soković Bajić, Svetlana; Jovanović, Živko; Matić, Ivana; Tolinački, Maja; Popović, Dušanka; Popović, Nikola; Terzić-Vidojević, Amarela; Golić, Nataša; Beškoski, Vladimir; Samardžić, Jelena (Frontiers in Microbiology, 2020)
In this study, for the first time, the comprehensive analysis of antiproliferative and antioxidant activities of ramson, followed by the analysis of its associated microbiota and health-promoting effects of lactic acid bacteria (LAB), was performed. Ramson (Allium ursinum) is recognized as a medicinal plant with a long history of use in traditional medicine due to its antimicrobial and antioxidant activity. In this study the influence of in vitro gastrointestinal digestion on the cytotoxic activity of A. ursinum extracts against human malignant cell lines was demonstrated. Seven sulfur compounds, the degradation products of thiosulfinates, including diallyl disulfide were shown to inhibit proliferation of malignant cells by inducing accumulation within G2/M phase as well as to induce apoptosis through activation of caspase-3 and mitochondrial signaling pathway. Further, the A. ursinum microbiota, particularly LAB with potential probiotic effects, was analyzed by culture-dependent method and culture-independent method [denaturing gradient gel electrophoresis (DGGE)]. The obtained results revealed that the most abundant genera were Streptococcus, Lactobacillus, and Bacillus. The Lactobacillus genus was mainly represented by L. fermentum. The pulsed-field gel electrophoresis (PFGE) analysis revealed the presence of two PFGE pulsotypes. The probiotic potential of the strain L. fermentum BGSR163 belonging to PFGE pulsotype 1 and the strain L. fermentum BGSR227 belonging to the PFGE pulsotype 2 was characterized. The results revealed that both strains are safe for human use, successfully survive the simulated gastrointestinal conditions, have potential to transiently colonize the gastrointestinal tract (GIT) and have a protective immunomodulatory effect, inducing the production of proinflammatory cytokine IL17 and regulatory cytokine IL10, while decreasing the production of proinflammatory cytokine IFN-γ. In conclusion, the results of this study suggest that consumption of A. ursinum might have health-promoting properties, including anticancer effects, while L. fermentum strains isolated from A. ursinum leaves could be used as probiotics for human consumption.